Modeling Rugose Spiraling Whitefly Infestation on Coconut Trees Using Delay Differential Equations: Analysis via HPM (European Journal of Pure and Applied Mathematics, 2024)
In this paper, a delay - induced pest control model is proposed. We have introduced a time delay in healthy trees and whitefly population in the infected tree density of the proposed system of equations to reduce the probability of healthy trees becoming infected, as well as the level of infection. We have analyzed the impact of time delay on the stability of the equilibrium and establish requirements to verify its asymptotic stability over all delays. The solutions of this system of non-linear ordinary differential equations(ODEs) and delay differential equations(DDEs) are presented by using homotopy perturbation method(HPM). Numerical simulation is also obtained for the same model of both ODE and DDE by using MATLAB software. The proposed method works very well and is easy to use, as shown by these findings. Our aim is to control the spread of whitefly such that harvest is not affected.
Keywords: Pest control model; Non linear differential equation; Delay differential equation; Homotopy perturbation method; Numerical simulation